Taxing the Good? Distortions, Misallocation, and Productivity in Sub-Saharan Africa - Cirera, Xavier; Fattal Jaef, Roberto N.; Maemir, Hibret B. (World Bank, Washington, DC, 2017)
This paper uses comprehensive and comparable firm-level manufacturing census data from four Sub-Saharan African countries to examine the extent, costs, and nature of within-industry resource misallocation across heterogeneous firms. The paper finds evidence of severe misallocation in which resources are diverted away from high-productivity firms toward low-productivity ones in all four countries, although the magnitude differs across countries. The paper shows that a hypothetical reallocation of resources that equalizes marginal returns across firms would increase manufacturing productivity by 31.4 percent in Cote d'Ivoire and as much as 162.7 percent in Kenya. The paper emphasizes the importance of the quality of the underlying data, by comparing the results against those from the World Bank Enterprise Surveys. The comparison finds that the survey-based results underestimate the extent of misallocation vis-a-vis the census. Finally, the paper finds that the size of existing distortions is correlated with various measures of business environment, such as lack of access to finance, corruption, and regulations.